Carbonation Reaction of Epoxidized Linseed Oil: Comparative Performance of TBABr and TBAI as Catalysts - Juan F. Nieto-Alarcón; David A. González; Enrique Vigueras-Santiago; Susana Hernández-López (Journal of Chemistry)
Cyclic carbonates are considered to be green nontoxic intermediates with important applications in polymer synthesis and fuel additives and as polar solvents with high boiling points. The carbonation of epoxidized vegetable oils is a very important step in the synthesis of nonisocyanate polyurethane. This reaction is usually performed with carbon dioxide in the presence of an ionic liquid that acts both as solvent and catalyst, with the most studied catalyst being tetra-n-butylammonium bromide (TBABr). Most of the works have reported high yields and good carbonation conversions. In addition, studies with tetra-n-butylammonium iodide (TBAI) as the catalyst have shown it to improve the conversion in the carbonation of short-chain epoxides but not of fatty acid esters and in some vegetable oils. In the current study, the carbonation of epoxidized linseed oil (ELO) (5.8 epoxide group per molecule) was carried out in an autoclave-type reactor under a carbon dioxide atmosphere (60 psi) and the variables evaluated were the reaction temperature (110°C and 140°C), catalyst load (2.5 mol% and 5.0 mol%), reaction time (24 h and 48 h), and catalyst type (TBABr and TBAI). The results of the study showed that the temperature was the most important factor affecting the reaction. However, halohydrins and ketones were also found to have formed from side reactions promoted mainly by TBAI at 140°C and were identified and quantified using FTIR-HATR, 1H-NMR, and 13C-NMR spectroscopy techniques. The best results namely, 100% conversion, 87.9% carbonation, and 87.9% selectivity, with relatively few side reactions (1.7% halohydrins and 1.7% ketones)were: 2.5 mol% of TBABr, a temperature of 110°C, and a reaction time of 24 h. The results also showed that using TBAI as the catalyst increased the frequency of undesirable side reactions during the carbonation of ELO.